Tyrian purple: an ancient natural dye for cross-conjugated n-type charge transport. Issue 12 (8th March 2021) - Fallon, Kealan J.; Wijeyasinghe, Nilushi; Leventis, Anastasia; Marin-Beloqui, Jose M.; Toolan, Daniel T. W.; Al-Hashimi, Mohammed; Clarke, Tracey M.; Anthopoulos, Thomas D.; Bronstein, Hugo
Abstract : N-type charge transport from cross-conjugated polymers derived from an ancient dye. Abstract : Herein, we present two novel organic semiconducting polymers synthesised from an ancient dye. By employing cross-conjugation within the polymer backbone as a synthetic strategy, we are able to engineer optical gaps such that the novel materials absorb over the entire visible spectrum. The cross-conjugated polymers exhibited relatively high n-type charge transport performance in organic field-effect transistors, a rare characteristic for this type of polymer. Quantum chemical calculations provide insight into this behaviour, suggesting that, whilst conjugation along the HOMO is indeed inhibited via molecular design, these materials possess highly delocalized LUMOs, facilitating high n-type charge transport.